2021
DOI: 10.1016/j.nbd.2021.105254
|View full text |Cite
|
Sign up to set email alerts
|

Facilitation of GluN2C-containing NMDA receptors in the external globus pallidus increases firing of fast spiking neurons and improves motor function in a hemiparkinsonian mouse model

Abstract: Globus pallidus externa (GPe) is a nucleus in the basal ganglia circuitry involved in the control of movement. Recent studies have demonstrated a critical role of GPe cell types in Parkinsonism. Specifically increasing the function of parvalbumin (PV) neurons in the GPe has been found to facilitate motor function in a mouse model of Parkinson’s disease (PD). The knowledge of contribution of NMDA receptors to GPe function is limited. Here, we demonstrate that fast spiking neurons in the GPe express NMDA recepto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 42 publications
1
10
0
Order By: Relevance
“…32 Moreover, the administration of DCS or AICP into the globus pallidus externa (GPe) was shown to improve the motor function in a mouse model of Parkinson's disease. 33 These observations demonstrate the potential for GluN2-specific Gly site agonists as modulators of NMDA receptors. Apart from AICP, analogues 6 and 7 are GluN1/2C superagonists with moderate potencies (EC 50 = 1.97 and 0.32 μM at GluN1/2C, respectively) and different agonist efficacy profiles across NMDA receptor subtypes compared to AICP.…”
Section: ■ Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…32 Moreover, the administration of DCS or AICP into the globus pallidus externa (GPe) was shown to improve the motor function in a mouse model of Parkinson's disease. 33 These observations demonstrate the potential for GluN2-specific Gly site agonists as modulators of NMDA receptors. Apart from AICP, analogues 6 and 7 are GluN1/2C superagonists with moderate potencies (EC 50 = 1.97 and 0.32 μM at GluN1/2C, respectively) and different agonist efficacy profiles across NMDA receptor subtypes compared to AICP.…”
Section: ■ Introductionmentioning
confidence: 82%
“…The nRT neurons are enriched with GluN2C-containing NMDA receptors that are proposed to regulate corticothalamic and thalamocortical communication . Moreover, the administration of DCS or AICP into the globus pallidus externa (GPe) was shown to improve the motor function in a mouse model of Parkinson’s disease . These observations demonstrate the potential for GluN2-specific Gly site agonists as modulators of NMDA receptors.…”
Section: Introductionmentioning
confidence: 93%
“…In the spinal cord, GluN2C was weakly detected in the dorsal horn and nonneuronal cells in white and gray matter in the lumbar region (Tolle et al, 1993;Sundstrom et al, 1997;Shibata et al, 1999;Akesson et al, 2000) as well as the ventral horn early in postnatal development (Stegenga and Kalb, 2001), but was not detectable in the cervical spinal cord (Watanabe et al, 1994). Functional studies utilizing GluN2C-selective pharmacology support neuronal expression in the cerebellum, thalamus, and globus pallidus (Fernandez et al, 2017;Bhattacharya et al, 2018;Liu et al, 2019bLiu et al, , 2021.…”
Section: Developmental Expression Of Kainate Receptor Subunitsmentioning
confidence: 99%
“…We found that 10 ms glutamate puffs reliably elicited EPSCs in VIP neurons (Figure 2B). We next performed puffs in the presence of 1.5 µM PPDA, a GluN2C/D-selective antagonist (Lozovaya et al, 2004;Li et al, 2020;Jing et al, 2022), and then in the presence of 20 µM CIQ, a GluN2C/D-selective positive allosteric modulator (Feng et al, 2014;Zhang et al, 2014;Nouhi et al, 2018;Liu et al, 2021). PPDA significantly decreased the amplitude (LMM: β = -29.95, p = 1.44e-07), halfwidth (β = -33.79, p = 2.85e-09), rise time (β = -23.71, p = 1.64e-06) and decay time constant (β = -36.78, p = 2.08e-05) of the elicited EPSCs, while CIQ significantly enhanced the amplitude (β = 24.13, p = 1.69e-05) and halfwidth (β = 16.88, p = 0.0017) (Figure 2C,D).…”
Section: Resultsmentioning
confidence: 99%